Violent Utopia : Dispossession and Black Restoration in Tulsa - Lewis, Jovan Scott (Book collections on Project MUSE., 2022)
"Violent Utopia traces the long history of the 1921 Tulsa Race Massacre from the migration of Black freed slaves to Oklahoma Indian Territory to contemporary efforts to rebuild Black prosperity in Tulsa. In doing so, Jovan Scott Lewis resists the temptation to exceptionalize both the violence of the 1921 massacre and the utopia of Tulsa's "Black Wall Street." Both, Lewis argues, exist in larger structures of anti-Black violence and dispossession, expulsion and segregation. Therefore the devastation of Tulsa's Greenwood district owes as much to Jim Crow enclosure and later urban renewal programs as the spectacular violence of the massacre. Violent Utopia illustrates how the North Tulsa community reconciles the inheritance of violence and freedom that form the very condition of their geography. As such, the book argues that the geography of North Tulsa, as a site of sovereign belonging, is the basis on which Black Tulsans will repair the promise of Greenwood"--